REFLEKSI PEMBELAJARAN JARAK JAUH SELAMA MASA PANDEMI COVID-19 PADA MATA PELAJARAN BIOLOGI KELAS X DI SMA NEGERI 2 MEDAN TP. 2020/2021 - Simbolon, Jimmy Francius (Jurnal Ilmiah Aquinas, 2021)
This research is a descriptive study that aims to obtain reflections on distance learning during the Covid-19 pandemic in Class X biology subjects at SMA Negeri 2 Medan TP. 2020/2021. The research subjects were students of class X. The research instrument was a questionnaire given to students online in a google form format. The results showed that: Distance Learning (PJJ) in Biology subjects at SMA Negeri 2 Medan TP. 2020/2021 has been carried out well. Most students are not accompanied during PJJ because both parents/guardians work, do not understand the material and there are already other people accompanying them, namely older siblings, other family members, and tutors. Most of the students do not understand the lesson well. Students can use online and offline learning tools well which are supported by environmental conditions at home to improve concentration. Most students are ready to study back at school at the TP. 2021/2022.